(untitled) (Shahroud Journal of Medical Sciences, 2021)
Background: Pregnancy with the help of a third party, including the use of sperm, oocyte, embryo, and uterus, can be considered as an option for some infertile couples. Due to the important role of health professionals in infertility treatments, their attitudes are of particular importance in the acceptance or rejection of fertility suggestions involving the help of a third party. This study aimed to determine the attitudes of medical students at medical universities in Tehran toward third-party reproduction. Methods: This descriptive cross-sectional study was carried out at the Medical University of Tehran in 2018. Medical students (n=187) filled out the questionnaire, which consisted of two parts: the demographic characteristics of the research subjects and the questionnaire consisted of 76 questions about attitudes toward third-party reproduction. The content and face validity of the questionnaire were determined, and test-retest reliability of the questionnaire was established (0.89). Results: According to gender, participants’ attitudes toward childbearing, the importance of genetic dependency between parents and children, law issues, anonymity in donation programs, parental affection, the importance of the recipient's and donor's characteristics, surrogacy, gamete, and embryo donation were all statistically non-significant (Pvalue>0.05). According to age and also to year of entering the university, participants’ attitude only toward childbearing was statistically significant (Pvalue= 0.018 and 0.01, respectively). Conclusion: Since medical school students may set on the road to a specialty associated with infertility and its ramifications, it’s better to educate our soon-to-be health system professionals on all necessary aspects of infertility and third-party reproduction. Key Words: Attitude; Donor Conception; Infertility; Medical Students; Assisted Reproductive Technique.